Self-regulated learning by writing learning protocols: Do goal structures matter?. (October 2021) - Moning, Jasmin; Roelle, Julian
Abstract: Having students write learning protocols is an established follow-up task to course work that elicits processes of self-regulated learning. To date, a wealth of research has focused on optimizing the learning protocol task itself by integrating instructional support measures such as prompts. By contrast, research that focuses on optimizing the context in which learning protocol writing is embedded is widely missing. In the present study, we approached this gap by focusing on the role of the contextual factor goal structure . Specifically, in an experiment with N  = 166 high school students we tested whether embedding the learning protocol task in a mastery goal structure would be more beneficial than embedding it in a performance goal structure. The mastery goal structure fostered metacognitive processes, learning outcomes, and learning efficiency. We conclude that considering contextual factors such as the goal structure is crucial for understanding and optimizing the effects of learning protocols. Highlights: We varied the goal structure in which learning protocol writing was embedded. A mastery goal structure had positive effects in learning protocol writing. A mastery goal structure fostered metacognitive processes during writing. A mastery goal structure fostered conceptual knowledge after writing. A mastery goal structure fostered learning efficiency during writing.